Now you see it, now you don't: An unusual case of hemoperitoneum in a patient with cirrhosis - Joshua Garmatter; Thomas Gezella; Carol Cunningham (JEM Reports)
Background: Patients with cirrhosis are at risk for developing a number of complications, including hepatocellular carcinoma (HCC). The rupture of a neoplastic lesion can lead hemoperitoneum. Though rare, spontaneous intraabdominal bleeding is potentially fatal and requires prompt treatment. Computed tomography is the preferred imaging modality due to its ability to reveal the extent and source of the patient's bleeding. Case report: We present an unusual case of a patient with cirrhosis presenting to the emergency department with chest and abdominal pain who was found to have hemoperitoneum from an apparent ruptured vessel within a HCC mass. While undergoing evaluation, the patient had spontaneous cessation of his bleeding. Why should an emergency physician be aware of this?: Spontaneous hemoperitoneum resulting from HCC rupture is a rare and potentially fatal complication if not recognized promptly. This case illustrates the need for vigilance in treating this patient population and the complexity of their hemostatic status.